2015
DOI: 10.1302/0301-620x.97b2.34926
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship of the cementless Spotorno femoral component in patients under 50 years of age at a mean follow-up of 18.4 years

Abstract: The long-term survival of the cementless Spotorno CLS femoral component in patients aged > 50 years at the time of arthroplasty was investigated. Survivorship analysis of a consecutive series of 85 patients (100 hips; under 50 years of age at a mean follow-up of 18.4 years (16.3 to 20.8)) was performed. The clinical and radiographic outcomes were satisfactory. The overall rate of survival of the femoral component was 93.5% (95% confidence interval (CI), 90.9 to 96.1) after 19 years. Survival with revision for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…This is in concordance with other long-term studies of the CLS stem. For example, Biemond et al (16) report a 93.5% survival at 18.4 years of follow-up, Evola et al (17) reported 91.5% survivorship at a minimum of 21 years of follow-up, and Streit et al (18) 86% with 22 years of follow-up. Our results are also comparable with those of other reliable cementless stems in young patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is in concordance with other long-term studies of the CLS stem. For example, Biemond et al (16) report a 93.5% survival at 18.4 years of follow-up, Evola et al (17) reported 91.5% survivorship at a minimum of 21 years of follow-up, and Streit et al (18) 86% with 22 years of follow-up. Our results are also comparable with those of other reliable cementless stems in young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although used for more than two decades, studies on CLS stem survival cementless extending into third decade in young patients are relatively rare compared to cemented implants 7, 8, 9, 10, 11, 12, 13. We performed a retrospective study to report the mid-long term results and survivorship analysis of CLS stem in patients younger than 50 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…As Journal of Orthopaedic Surgery 26 (1) the proximal femoral morphology and bone mineral content of Asians and Westerners are different, potentially influencing the outcomes of hip components, 3 we investigated the long-term performance of the CLS stem with a mean follow-up period of 20.1 years. We found excellent stem survival rates, which were slightly better than those reported in previous studies 1,6,19 and similar to those in a minimum 10-year follow-up study. 9 Although opinion is divided, undersized stems, 20 varus stem alignments, 21 and previous osteotomies 1 were reported to have negative influence on stem survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although opinion is divided, undersized stems, 20 varus stem alignments, 21 and previous osteotomies 1 were reported to have negative influence on stem survival rates. In our study, we found that varus stem alignment had a statistically significant negative influence on stem survival rate, similar to the results of Mallory et al and Vresilovic et al 21,22 However, our study confirmed that undersized stems and previous osteotomies did not compromise stem survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation